Students’ Views toward the use of Think-Pair-Share Strategy on students’ oral communication skill in an EFL context - Darmawan, Yohanes Richardus Ricky; Lestariningsih, Fransisca Endang (Universitas Pendidikan Mandalika, 2023)
The purpose of this study was to investigate students’ views toward the use of the Think-Pair-Share teaching strategy on their oral communication skills. The primary focus of this study was to investigate the possible effect of the Think-Pair-Share teaching strategy on the students’ oral communication skills. The secondary purpose was to know the students’ view toward the application of this teaching strategy based on their experiences. Based on the purpose of the study, investigations were done by using interviews. The interviews were done with four participants consisting of the chosen students based on their experience. Zoom application was used during the interviews. Audio recordings were transcribed into text and translated into English. The keywords extracted from the transcriptions were used to determine the coding. Furthermore, the themes were reported as the study's findings and then supported by previous research. The result showed that the Think-Pair-Share teaching strategy could help the students enhance their self-confidence and could be helpful in improving their oral communication skills on condition that the students use English as the medium of discussion. Meanwhile, the findings for the secondary purpose revealed that the students found this teaching strategy was quite helpful in improving their teamwork and critical thinking skill. The students also felt that this teaching strategy offered varied activity, thus making the class become less boring. The findings reveal that the Think-Pair-Share teaching strategy needs to be implemented carefully in order to achieve its full effectiveness. As the implication, the Think-Pair-Share teaching strategy could be applied considering the advantages and the effects for the students.